Efektivitas Blended Learning dalam Pelatihan Dasar CPNS: Studi Komparatif Hasil Belajar Berdasarkan Lokasi Domisili Peserta - Nugraha, Albertus Nur Cahya; Kamaliah, Naily (Tatar Pasundan: Jurnal Diklat Keagamaan, 2025)
Basic Training (Latsar) for Civil Servant Candidates (CPNS) is a critical element in developing the competencies of Indonesia's civil servants. This study aims to analyze the effectiveness of a blended learning approach in improving learning outcomes of Latsar participants based on their domicile, either domestically or abroad. A quantitative approach was employed using descriptive and inferential statistical analysis. Data were collected from 158 participants of the 2024 BRIN CPNS Latsar program and analyzed through independent sample t-tests and binary logistic regression. The findings reveal that participants residing abroad achieved significantly higher scores in independent learning (MOOC), whereas domestic participants performed better in actualization reports. No significant differences were found in e-learning, classical training, or actualization design seminars. Logistic regression results indicate that only the actualization report assessment significantly influenced participants’ graduation outcomes. These results highlight the importance of tailored support for overseas participants and the essential role of mentors and coaches in guiding actualization-based learning. The study recommends enhancing coaching strategies to ensure equitable learning outcomes regardless of participant location.Keywords: CPNS Basic Training; Blended Learning; Learning Outcomes; Participant Domicile; MOOC; Actualization